Peran faktor fisik-kimia habitat terhadap pertumbuhan mangrove di delta cisanggarung pantai utara Jawa Tengah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
The mangrove rehabilitation using Rhizophora mucronata in Delta Cisanggarung on the North Coast of Central Java showed variation in the density, height, and diameter of the species although they were of the same age. The response might be influenced by some physical and chemical factors. The research goals were to know the variation of physical and chemical factors of habitat in the mangrove rehabilitation area. The Coast line on the mangrove was divided into 3 section, started eastwards from the estuary with a range of respectively, 0-300m, 300-600m, and 600-900rn. Density, height and diameter of trees as well as physical and chemical factors such as salinity, temperature, pH, mud thick, organic matter, DO and the content of N,P,K in each section were measured. The data were analyzed using variance analysis, regression analysis and cluster analysis. Results showed that physical and chemical factors in the 300-600m and 600900m section were not significantly different. However, the physical and chemical factors in 0-300m section were not significantly different with those in 300-600m section and 600-900m section. The important factors in the 0-300m section included pH, organic matter, DO, N,P,K and salinity, whereas the important factor in the 300600m section were pH, K, organic matter and DO. The important factors in the 600900m section were pH, N and salinity. The 300-600m section and 600-900m section showed a similarity in the physical and chemical factors compared with the other section.